2012
DOI: 10.1134/s1069351312050035
|View full text |Cite
|
Sign up to set email alerts
|

The phenomenon of synchronism in the magnetosphere-technosphere-lithosphere dynamical system

Abstract: Synchronism in geophysical events became the focus of the research in the second half of the last century when the study of this subject was almost simultaneously launched in the former Soviet Union and the United States. Interest in this issue has recently risen after a 20 year hiatus. The impetus was provided by the successful application of the synchronous detection technique to analyzing vast volumes of digital data on the electromagnetic waves in the magnetosphere and on the earthquakes. These studies rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 21 publications
(21 reference statements)
1
0
0
Order By: Relevance
“…Power line generated artificial signals in the 1 Hz frequency range were detected over distances of more than 1500 km, and such distances were never reported in case of heating experiments [Ermakova et al, 2006]. Our modeling has shown that an installation with scale >100 km and ≥100 A current is sufficient under favorable conditions to stimulate emission in the Pc1 The modeling results give some support to the puzzling observations of "weekend effect" and "time mark effect" in ground Pc1 activity [Guglielmi & Zotov , 2012]. The electric power consumption is known to have peaks around tops of the hour.…”
Section: Discussionsupporting
confidence: 66%
“…Power line generated artificial signals in the 1 Hz frequency range were detected over distances of more than 1500 km, and such distances were never reported in case of heating experiments [Ermakova et al, 2006]. Our modeling has shown that an installation with scale >100 km and ≥100 A current is sufficient under favorable conditions to stimulate emission in the Pc1 The modeling results give some support to the puzzling observations of "weekend effect" and "time mark effect" in ground Pc1 activity [Guglielmi & Zotov , 2012]. The electric power consumption is known to have peaks around tops of the hour.…”
Section: Discussionsupporting
confidence: 66%